2012
DOI: 10.4253/wjge.v4.i8.347
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of endoscopy in the management of eosinophilic esophagitis

Abstract: Eosinophilic esophagitis (EoE) is a clinicopathological entity characterized by a set of symptoms similar to gastroesophageal reflux disease and eosinophilic infiltration of the esophageal epithelium. EoE is an emerging worldwide disease as documented in many countries. Recent reports indicate that EoE is increasingly diagnosed in both pediatric and adult patients although the epidemiology of this new disease entity remains unclear. It is unclear whether EoE is a new disease or a new classification of an old e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 48 publications
0
2
0
4
Order By: Relevance
“…EoE has been documented in most racial groups, although many studies have reported predominance in Caucasian males [22] . The prevalence of EoE in an outpatient population undergoing upper endoscopy was reported 0.4%-0.5% [23] , but EoE was found in 12% of …”
Section: Discussionmentioning
confidence: 99%
“…EoE has been documented in most racial groups, although many studies have reported predominance in Caucasian males [22] . The prevalence of EoE in an outpatient population undergoing upper endoscopy was reported 0.4%-0.5% [23] , but EoE was found in 12% of …”
Section: Discussionmentioning
confidence: 99%
“…Beschrieben werden auch eine "Krepppapier-Schleimhaut", eine erhöhte Vulnerabilität der Ösophagusschleimhaut mit Auftreten von longitudinalen Schleimhauteinrissen während der Endoskopie und Schatzki-Ringe. Weitere histologische Befunde neben der erhöhten Eosinophilenzahl sind das Vorkommen eosinophiler Mikroabszesse, eosinophile Degranulation, oberflächliche Verteilung der Eosinophilen und Hyperplasie der epithelialen Basalzone [1,4,7]. Optimal ist es, wenn die Biopsien nach 4-wöchiger Vorbehandlung mit einem Protonenpumpeninhibitor (PPI) entnommen werden, da auch bei GERD im distalen Ösophagus ein eosinophiles Entzündungsinfiltrat auftreten kann.…”
Section: Das Pflegepersonal In Rettungsstelle Undunclassified
“…Auch bei Fehlen typischer endoskopischer Befunde sollten Proben aus der normalen Schleimhaut entnommen werden. Sinnvoll sind mindestens 5 Biopsien aus mehreren Ösophagusabschnitten [3,4,7]. Zusätzliche Biopsien aus Magen und Duodenum zielen auf die mögliche Diagnose eines Morbus Crohn oder einer eosinophilen Gastroenteritis [3,4].…”
Section: Das Pflegepersonal In Rettungsstelle Undunclassified
See 1 more Smart Citation
“…In children, commonly reported symptoms include feeding difficulties, vomiting, and failure to thrive 4, 5, 6, 7, 8, 9, 10, 11. Among the adolescent and adult populations with EoE, dysphagia, vomiting, and chest pain are the common presenting symptoms.…”
Section: Introductionmentioning
confidence: 99%